NURSING STUDENTS’ ALUMNI NEEDS IN STUDYING ENGLISH AT SMK KESEHATAN DHARMA ANANDA BUNGO - Fitriyani Fitriyani; Yulhenli Thabran; Nunung Fajaryani (JAMBI-ENGLISH LANGUAGE TEACHING, 2023)
Abstract SMK Kesehatan Dharma Ananda is the only health vocational school in Bungo Regency. It has two majors, namely Pharmacy major and nursing major. Learning English at Vocational High School uses the same curriculum as Senior High School, namely K13. The English Materials they learned were general English, for example learning about general vocabulary; the topic not specific to their major; and others. The purpose of this research was to investigate the needs of nursing students alumni at SMK Kesehatan Dharma Ananda Bungo Regency in learning English. This study used a descriptive method with a qualitative approach. A questionnaire and interview were conducted to gather the data. 15 Alumni students of nursing at SMK Kesehatan Dharma Ananda Bungo participated in this research. 6 out of 15 students were also interviewed to clarify needs. The findings of this research showed that the nursing students at SMK Kesehatan Dharma Ananda Bungo needed English material according to their major. Their needs in learning English are to read, write, speak, and listen in English well in the field of nursing. The results of the research showed that the needs of the nursing students alumni at SMK Kesehatan Dharma Ananda Bungo is learning materials related for nursing students but unfortunately, the students are still provided with general English learning materials. Keywords: Needs, Nursing Students, ESP, Vocational High School, Learning English